2014
DOI: 10.1093/molehr/gau032
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-7 is important for normal uterine repair following menstruation

Abstract: Menstruation involves the shedding of the functional layer of the endometrium in the absence of pregnancy. At sites where tissue shedding is complete, re-epithelialization of the tissue is essential for repair and termination of bleeding. The complement of growth factors that mediate post-menstrual endometrial repair are yet to be completely elucidated. Galectins regulate many cell functions important for post-menstrual repair, such as cell adhesion and migration. Galectin-7 has a well characterized role in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…In addition, elevated galectin-7 expression is associated with uterine repair after menstruation (Evans et al 2014 ), miscarriage (Menkhorst et al 2014b ), and preeclampsia (Menkhorst et al 2014a ). Many of these observations relate to the proposed role for galectin-7 in reepithelialization associated with wound repair (Panjwani 2014 ).…”
Section: Galectinsmentioning
confidence: 99%
“…In addition, elevated galectin-7 expression is associated with uterine repair after menstruation (Evans et al 2014 ), miscarriage (Menkhorst et al 2014b ), and preeclampsia (Menkhorst et al 2014a ). Many of these observations relate to the proposed role for galectin-7 in reepithelialization associated with wound repair (Panjwani 2014 ).…”
Section: Galectinsmentioning
confidence: 99%
“…However, in cancerous renal tissue, galectin-7 may manifest completely different functions. Take the uterus for examples, galectin-7 up-regulate MMP-9 expression, thereby promotes tumor progression and metastasis in cervical squamous carcinoma [25], while in normal uterus, it promotes uterine repair following menstruation [26]. Our study revealed the correlation of galectin-7 expression and overall survival in non-metastasis ccRCC, which shed a light on the potentially different functions of galectin-7 in ccRCC from normal kidney tissues.…”
Section: Discussionmentioning
confidence: 70%
“…It was hypothesized that the recombinant galectin-7 utilized in the present study would have extra-and intra-cellular actions. We have previously demonstrated that endometrial epithelial cell lines display functional responses to exogenous galectin-7 (14,15). Whether exogenous galectin-7 is endocytozed into EC cells is yet to be determined: An increase in intracellular galectin-7 mRNA in Ishikawa cells 24 h after galectin-7 treatment was not identified (data not shown); however, only one time-point was used and intracellular protein was not measured.…”
Section: Discussionmentioning
confidence: 97%
“…To mimic the rising levels of galectin-7 determined in EC, EC cell lines were treated with recombinant galectin-7 for the in vitro functional assays. The concentration used (1 µg/ml) was determined from the manufacturer's protocols and dose-response trials in previous studies (14,15), but it is notable that extracellular galectin-7 remains to be identified in EC. Galectin-7 could not be detected in the endometrial epithelial EC cell line conditioned media (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation